In situ diagnostics of damage accumulation in Ni-based superalloy - Kageyama, K (2020)
There has been a significant interest in capturing how the damage is initiated and accumulated in polycrystalline Ni-based superalloys while applying thermal and mechanical impact – tensile and creep loading at 800◦C. This is because the turbine component in jet propulsion or power generation these materials applied can experience such environments while in service and need to avoid unexpected degradation and failure causing severe accidents. In situ damage observation techniques required to be developed to understand the sequential mechanisms of damage growth even in such complicated environment.